Aspectos neuropsicológicos e comportamentais associados à Doença de Gaucher tipo 1: relato de uma série de casos - Sakata, Edna Tieme [UNIFESP] (2015)
Gaucher disease type I - (DG) is an inborn error of metabolism (IEM), incidenting the group of lysosomal diseases (DL), which is caused by mutation in the gene of acid beta-glucosidase (GBA) which determines disability of enzyme activity. It is a rare and chronic disease, whose clinical manifestations include hematological, visceral and bone alterations, which may result in limitations on a person's quality of life. Although type1 DG is not associated with neurological manifestations, recent surveys have shown deficits in attention and memory in adult patients. Studies of the neurocognitive and behavioral development in children and adolescents furthermore are scarce. The main objective of this study was to report a case series and review aspects of cognitive and behavioral functioning in a sample (predominantly pediatric) patients with type 1 GD under enzyme replacement therapy (ERT), followed at the Reference Center Inborn Errors of Metabolism (CREIM) of the Federal University of São Paulo (Unifesp). The patients were submitted to an evaluation their intellectual performance, cognitive functions such as memory, attention, executive functioning, and also the investigation of adaptive skills, having been based on the behavioral scale, Child Behavior Cheklist (CBCL). The results were analyzed descriptively, considering the sample as a whole and individually, whereby it sought to reflect on the possible predominance of cognitive and behavioral problems and associations of clinical and environmental influences. We evaluated nine patients, aged from 6 to 20 years, five male. The results have shown average intellectual performance and the appropriate development of adaptive skills in all evaluated. The analysis suggested that had better development of the verbal skills compared to non-verbal. The alterations in executive functioning, including the inhibitory control abilities (occurring in 6/9 participants) and a delay of the responses in sustained attention tests (5/9) were the most relevant findings in. There were no evident behavioral problems. The two participants had a higher number of results low performers in the evaluations were diagnosed later and a longer time interval between age at onset of symptoms and the treatment. Because of this, it is suggested that the clinical variables such as age-related diagnosis and the beginning treatment appears to have an impact on neuropsychological abnormalities.